Race and sex differences in dropout from the STRRIDE trials - Collins, Katherine A.; Huffman, Kim M.; Wolever, Ruth Q.; Smith, Patrick J.; Siegler, Ilene C.; Ross, Leanna M.; Jakicic, John M.; Costa, Paul T.; Kraus, William E. (Frontiers in Sports and Active Living, 2023)
To determine if race and sex differences exist in determinants and timing of dropout among individuals enrolled in an exercise and/or caloric restriction intervention.Methods: A total of 947 adults with dyslipidemia (STRRIDE I, STRRIDE AT/RT) or prediabetes (STRRIDE-PD) were randomized to either inactive control or to of 10 exercise interventions, ranging from doses of 8 to 23 kcal/kg/week, intensities of 50% to 75%V O2 peak, and durations of 6 to 8 months.Two groups included resistance training, and one included a dietary intervention (7% weight loss goal).Dropout was defined as an individual withdrawn from the study, with the reasons for dropout aggregated into determinant categories. Timing of dropout was defined as the last session attended and aggregated into phases (i.e., "ramp" period to allow gradual adaptation to exercise prescription). Utilizing descriptive statistics, percentages were generated according to categories of determinants and timing of dropout to describe the proportion of individuals who fell within each category.Results: Black men and women were more likely to be lost to follow-up (Black men: 31.3% and Black women: 19.6%), or dropout due to work responsibilities (15.6% and 12.5%), "change of mind" (12.5% and 8.9%), transportation issues (6.3% and 3.6%), or reported lack of motivation (6.3% and 3.6%).Women in general noted lack of time more often than men as a reason for dropout (White women: 22.4% and Black women: 22.1%). Regardless of race and sex, most participants dropped out during the ramp period of the exercise intervention; with Black women (50%) and White men (37.1%) having the highest dropout rate during this period.These findings emphasize the importance of targeted retention strategies when aiming to address race and sex differences that exist in determinants and timing of dropout among individuals enrolled in an exercise and/or caloric restriction intervention.